Difficulties in the teaching of biological topics through outdoor activities - Lindio, Salvacion M. 1955- (1978)
This study was undertaken for a three-fold purpose: 1.)to obtain information as to what topics in the BSCS Philippine Adaptation Laboratory Manual and other biological topics are taught with outdoor activities and the strategies used to teach these topics; 2.) to identify the difficulties biology teachers encounter in teaching these topics with outdoor activities, and 3.) to obtain suggestions from the teachers how these difficulties may be overcome. Thirty eight Biology teachers served as the subjects. Data revealed that teachers use a variety of strategies; strategy on identifying, naming, classifying and collecting organisms predominates.
Vita.
Thesis (M.A.T. Biology)--University of the Philippines, Diliman.
Keywords: Biology -- Study and teaching (Secondary) -- Activity programs -- Philippines -- Albay; Biology teachers -- Philippines -- Albay; Outdoor education -- Philippines -- Albay